2009
DOI: 10.1186/1471-2407-9-316
|View full text |Cite
|
Sign up to set email alerts
|

The striking geographical pattern of gastric cancer mortality in Spain: environmental hypotheses revisited

Abstract: BackgroundGastric cancer is decreasing in most countries. While socioeconomic development is the main factor to which this decline has been attributed, enormous differences among countries and within regions are still observed, with the main contributing factors remaining elusive. This study describes the geographic distribution of gastric cancer mortality at a municipal level in Spain, from 1994-2003.MethodsSmoothed relative risks of stomach cancer mortality were obtained, using the Besag-York-Molliè autoregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 51 publications
(48 reference statements)
0
25
0
1
Order By: Relevance
“…The reasons that could make it difficult to establish a relationship between cancer and spatial risk factors include: i) the latency period of the disease (Jarup et al, 2002;Toledano et al, 2001); ii) the situation in which a factor identified in one geographic region may not have the same effect in another region due to the presence or absence of other factors (Aragones et al, 2009); or iii) the fact that most cancers result from a combination of several factors rather a single one (Klassen and Platz, 2006).…”
Section: Methods Appliedmentioning
confidence: 99%
“…The reasons that could make it difficult to establish a relationship between cancer and spatial risk factors include: i) the latency period of the disease (Jarup et al, 2002;Toledano et al, 2001); ii) the situation in which a factor identified in one geographic region may not have the same effect in another region due to the presence or absence of other factors (Aragones et al, 2009); or iii) the fact that most cancers result from a combination of several factors rather a single one (Klassen and Platz, 2006).…”
Section: Methods Appliedmentioning
confidence: 99%
“…No increased incidences of bladder or lung cancer have been noted in the districts of the DB (Lopez-Abente et al, 2006;Aragonés et al, 2009). However, Aragonés et al (2009) found a clear geographic pattern of gastric cancer incidence in Spain, with highest incidence coinciding with the DB. While gastric cancer has not been clearly linked to As exposure, environmental exposure via drinking water was highlighted as one possible cause of the distributions observed.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Geographic variations in gastric cancer incidence and mortality in terms of a north-south gradient have been reported in both the West and the East. (6)(7)(8) These variations may be related to differences in risk factors, such as the prevalence rate of H. pylori infection. Migration studies have shown that first-generation migrants from countries with a high incidence of H. pylori infection relocating to countries of low incidence rates had similar risks as that of the country of origin, but the incidence rate…”
Section: Epidemiological Trends In Gastric Cancermentioning
confidence: 99%